Relative growth and morphological sexual maturity of the crab Hepatus pudibundus (Herbst, 1785) (Decapoda: Aethridae) in southeast Brazil - Jaconis, Milena Silva [UNESP]; Nogueira, Caio Santos [UNESP]; Vieira Martins Rezende-Gois, Gabriel [UNESP]; Perroca, Julia Fernandes [UNESP]; Costa, Rogerio Caetano [UNESP] (Taylor & Francis, 2022)
The crab Hepatus pudibundus is a bycatch of the shrimp fishing industry, and despite having no commercial value, it is impacted by fishing activities. In this way, research about relative growth and sexual maturity can help to understand the life cycle of fisheries-affected species. Thus, the present study aimed to estimate morphological sexual maturity (MSM) and analyse the relative growth of a population of H. pudibundus. For morphometric analysis and MSM estimate, the following structures were measured: the carapace (CW) and abdomen width (AW), the left and right cheliped propodus length (LPL and RPL) and height (LPH and RPH) for both sexes, and the gonopodium length (GL) for males. No heterochely was observed for both sexes, but the propodus dimensions showed sexual dimorphism. Males attain MSM at 44.71 mm CW and females at 41.87 mm CW. Males and females showed higher growth rates in GL and AW, respectively, in the juvenile stage, suggesting a greater investment in the development of secondary sexual characteristics before MSM. The present study provides information on the growth pattern of the species, which is significant to the community structure of fishing areas and serves as a parameter for evaluating protective measures that have been implemented.
Keywords: Allometry; brachyura; ontogeny; reproduction